Monopolar diathermy used for correction of ankyloglossia - Tuli A; Singh A (Wolters Kluwer Medknow Publications, 2010)
Tongue tie, also known as ankyloglossia or ankyloglossia inferior, is a relatively common finding in pediatric surgical outpatient clinics. It occurs as a result of a short, tight, lingual frenum causing tethering of the tongue tip. It is a common oral finding in infants and children, which is often neglected. Although most cases resolve or are asymptomatic, some patients develop articulation problems and other concerns related to poor tongue-tip mobility. In this article, we report on a 5-year old girl with a tongue tie, who underwent frenectomy using monopolar diathermy under local anesthesia without any postoperative complication.